Promessas antológicas: o conto latino-americano contemporâneo a partir de algumas antologias - Wilson Alves-Bezerra (Estudos de Literatura Brasileira Contemporânea)
What do contemporary anthologies of Latin American literature portray in regards to the ways of reading, organizing and selecting the short contemporary narratives of Latin America? Some issues will be approached, grounded in consi- derations made over three recently published anthologies within this genre -Antologia panamericana ; Os outros: antologia de narrativa argentina contemporânea ; Les bonnes nouvelles de l ́Amérique latine . The issues are related to the market in fl uences, the criteria employed by anthologists and the endurance of fossilized views on the continental production such as the boom of Latin American Literature from the fi fties and the magical realism. Addressing, mainly, the criteria adopted by the anthology of Gallimard Publisher will yield re fl ection over the genre in our current context.